The Sectoral Classification of Intellectual Capital Value - Krzysztof Adam FIRLEJ; Mateusz MIERZEJEWSKI (Communications of International Proceedings, 2021)
The aim of the study is the sectoral typification of intellectual capital value measured by the VAIC method including the components of the index (physical capital CEE, human capital HCE, structural capital SCE) in the European Union countries, Iceland, Norway, Switzerland and Great Britain. The research hypothesis stating that the value of intellectual capital and its components is diversified across sectors due to their different activity profiles was verified positive. It implicates the necessity of competent management of expenditures proportions on the types of capital used in a business activity. In the classification process of individual sectors by the Ward’s method the highest average of intellectual capital measured by the VAIC method was obtained in Business Services, Communications, Computer Software, Media & Broadcasting and Property Services, which indicates the key role of intellectual capital in such kind of activities.
Keywords: intellectual capital; human capital; structural capital; value of intellectual capital; sectoral classification; VAIC method; Ward’s method